Minds and the intellectually disabled in Singapore: a multimedia project - Abdul Wahab Saul Hamid (2008)
The basic objective of this project is to raise public awareness about a group of people who have been neglected by the society-the intellectually Disabled (ID). Presented via CD-ROM.